Expert System for Troubleshooting Web-Based Lan Network Using Forward Chaining Method - Afrianto, Eko; Ayuningsih, Ekatri (Journal of Intelligent Systems and Information Technology, 2025)
This research develops an expert system for troubleshooting LAN networks using the forward chaining method at SMK PGRI Lumajang. With numerous devices connected simultaneously, including computers, tablets, and smart devices, the network may become congested, leading to slow data transfer and connectivity issues. This is especially problematic during peak hours when students and staff access online resources concurrently. The forward chaining method is an artificial intelligence approach in which the system uses given facts to reach a solution. Expert systems have become an important instrument in solving technical problems in various fields, including computer networks. This research discusses the development of an expert system for troubleshooting web-based LAN networks using the forward chaining method. The forward chaining method is an approach used in artificial intelligence where the system uses given facts to reach a conclusion or solution. Expert systems are developed by using web-based technology, allowing easy and fast access for users in various locations. It is hoped that the results of this research can contribute to increasing efficiency and effectiveness in handling LAN network troubleshooting problems at SMK PGRI Lumajang. Apart from that, it is also hoped that the application of the expert system can become a reference and guide for network technicians in solving complex problems